Human Resource Readiness And Digital Technology Utilization In Supporting The Performance Of Rollin’ MSME - Agoes Windarto; Sudarmiatin; Puji Handayati; Naswan Suharsono (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The rapid development of digital technology presents both opportunities and challenges for micro, small, and medium-sized enterprises (MSMEs), particularly in aligning human resource readiness with the increasing demands of digitalization. This study examines the current condition of human capital, digital technology utilization, and work motivation in Rollin’ MSME, Malang. Data were collected through surveys, interviews, and financial records covering monthly sales performance. Findings indicate that Rollin’ MSME faces significant human resource limitations, especially in digital literacy and participation in skill development, despite strong intrinsic motivation among some employees. Technology utilization is relatively high, with MSMEs adopting online sales platforms and basic digital administration; however, outcomes remain suboptimal due to inconsistent implementation. Financial analysis shows stable but moderate performance, with product sales dominated by cheese cake slices and potato donuts. Overall, the study highlights the need for strengthening HR capabilities and optimizing digital practices to enhance business performance.